Uso e apropriação dos espaços livres públicos e informais de uma área urbana em João Pessoa PB - Pizzol, Kátia Maria Santos de Andrade (2005)
The urban one inside of the physical aspect is constituted by built spaces and free spaces. These last ones are important in the question of the sustainable of the cities and in the improvement of the quality of life in the urban one. Inside of this context the present study it looks for to understand and to reflect on the availability, form of use, typology and the vegetal covering of the found free spaces in an urban area, located in the zone south-Southeast of the city of João Pessoa, composed for four quarters (Água Fria, Anatólia, Jardim Cidade Universitária and Jardim São Paulo), that still it has areas without occupation, thus constituting, a supply favorable to the real estate speculation, as also, presents in its structure examples of indifference with the question of the importance of these spaces for the recreation, mobility and conservation of the urban environment and its influences in the improvement of the quality of life. In accordance with the typology, uses and lacks found in the area, resultants of physical surveys, register photographic and search (interviews and questionnaires), it was gone deep reflection in the public sidewalks and in the informal spaces they appear in function of the necessity of the population. Thus, one concludes that the population perceives that its quality of life is related to the use forms and appropriation of these public spaces, for all the citizens, are healthful they, or with some difficulty of locomotion, propitiating the mobility inside of the urban one and guaranteeing to all, health, leisure, socialization and mainly, citizenship.